The Kindness Colder Than the Elements - Charles Noble (Mingling Voices, 2011)
These are poems that play with and in language, take pleasure in the sounds of words, poems that are propelled by puns. Yet even with this priority of sound and language, there are tender moments when the language does more than delight in itself, as though it has stumbled across lyric meaning accidentally." -Jay Gamble, University of Lethbridge . With wit and cunning, Noble's poems insinuate themselves into the mediations of "we use language" / "language uses us," into the objectification of "mind," into the struggles and cracking of systems. Cuing on Hegel's epochal revitalization of the syllogism, they begin with sentences-cum-arguments that issue from an everyman's intentions and insights, playing into and baiting the "sociality of reason." In the cut-up sentences then come the restless, accelerated themes-themes that exist only in their variations, ghosting into one another like the dusk and the dawn in a winging, distended now.